2011
DOI: 10.3952/lithjphys.51401
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport in modulation-doped InAlAs/InGaAs/InAlAs and AlGaAs/InGaAs/AlGaAs heterostructures

Abstract: The possibilities of enhancing the electron mobility and high-field drift velocity in channels of modulation-doped InAlAs/InGaAs and AlGaAs/InGaAs quantum wells by tuning interaction of electrons with interface phonons are tested and reviewed. A large increase in the mobility is achieved in a novel metamorphic In 0.7 Al 0.3 As/In 0.8 Ga 0.2 As structure with the high InAs content in the InAlAs barrier layer as well as in the Al x Ga 1-x As/In 0.2 Ga 0.8 As structure with the low AlAs content in the AlGaAs barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been observed that there is rise in electron mobility in In 0.7 Al 0.3 As/In 0.8 Ga 0.2 As system with rise in InAs content in the InAlAs barrier and in the Al x Ga 1-x As/In 0.2 Ga 0.8 As system with a decrease in AlAs content in the AlGaAs barrier. Also, it has been seen that by taking a thin layer of InAs in the In 0.52 Al 0.48 As/In 0.53 Ga 0.47 As quantum well system, the mobility enhances [27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that there is rise in electron mobility in In 0.7 Al 0.3 As/In 0.8 Ga 0.2 As system with rise in InAs content in the InAlAs barrier and in the Al x Ga 1-x As/In 0.2 Ga 0.8 As system with a decrease in AlAs content in the AlGaAs barrier. Also, it has been seen that by taking a thin layer of InAs in the In 0.52 Al 0.48 As/In 0.53 Ga 0.47 As quantum well system, the mobility enhances [27].…”
Section: Introductionmentioning
confidence: 99%
“…Twodimensional electron gas (2DEG) confined to a quantum well (QW) InGaAs demonstrates both high electron mobility and drift velocity. The most important factors that limit electron mobility μ e in HEMT are the polar optical phonon scattering [1,22] and remote ionized impurity scattering [3]. In order to improve μ e one should vary the design of the heterostructure, in particular the QW and the barrier layer.…”
Section: Introductionmentioning
confidence: 99%